Republic of Congo : Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2007)
This paper on the Republic of Congo's staff-monitored program (SMP) reports that the authorities and civil society pledged to work together to make resource management more transparent. The authorities have reached understandings with IMF staff on an SMP for April-September 2007. The SMP aims at making progress toward fiscal sustainability, enhancing public financial management, and improving governance and transparency. A solid track record of policy implementation in the context of the SMP would pave the way for discussions on a Poverty Reduction and Growth Facility arrangement to resume by end-2007.